Anxiety in young people with autism spectrum disorder: Common and autism-related anxiety experiences and their associations with individual characteristics. (July 2020) - Lau, Boon Yen; Leong, Ruth; Uljarevic, Mirko; Lerh, Jian Wei; Rodgers, Jacqui; Hollocks, Matthew J; South, Mikle; McConachie, Helen; Ozsivadjian, Ann; Van Hecke, Amy; Libove, Robin; Hardan, Antonio; et al.
Anxiety is common in autism spectrum disorder. Many anxiety symptoms in autism spectrum disorder are consistent with Diagnostic and Statistical Manual of Mental Disorders (5th ed.) anxiety disorders (termed "common" anxieties), but others may be qualitatively different, likely relating to autism spectrum disorder traits (herein termed "autism-related" anxieties). To date, few studies have examined both "common" and "autism-related" anxiety experiences in autism spectrum disorder. We explored caregiver-reported Spence Children's Anxiety Scale-Parent version data from a multi-site (United Kingdom, Singapore, and United States) pooled database of 870 6- to 18-year-old participants with autism spectrum disorder, of whom 287 provided at least one written response to the optional open-ended Spence Children's Anxiety Scale-Parent item 39 (" Is there anything else your child is afraid of ?"). Responses were thematically coded to explore (a) common and autism-related anxiety presentations and (b) their relationship with young people's characteristics. Nearly half of the responses were autism-related anxieties (mostly sensory, uncommon, or idiosyncratic specific phobias and worries about change and unpredictability). The other half described additional common anxieties not covered in the original measure (mostly social, weather and environmental disasters, and animals). Caregivers of participants who were more severely affected by autism spectrum disorder symptoms reported more autism-related, as compared to common, additional anxieties. Implications for the assessment and understanding of anxiety in autism are discussed.